(untitled) (International Journal of Engineering and Computer Science, 2024)
In today’s era of rapid technological advancements, organizations are increasingly embracing digital transformation as a pivotal strategy to enhance their competitiveness and operational efficiency. This paradigm shift towards digitalization entails the integration of advanced digital technologies into the fabric of organizational processes and systems. However, this transformative journey often unfolds in tandem with significant organizational change, reshaping not only operational workflows but also the very culture that underpins the workplace dynamics. This research article delves into the complex interplay between digital transformation initiatives and the overarching safety culture within organizations undergoing profound organizational change processes. Recognizing that safety culture constitutes a cornerstone of organizational well-being and performance, this study seeks to elucidate the multifaceted implications of digitalization on safety practices, attitudes, and behaviors in the workplace. Through a meticulous examination of the challenges, opportunities, and strategic imperatives inherent in the convergence of digital transformation and safety culture, this research endeavors to offer nuanced insights that can inform organizational decision-making and practice. By unpacking the intricacies of this nexus, the study aims to equip stakeholders with actionable knowledge and best practices conducive to nurturing a positive safety culture amidst the backdrop of digital transformation endeavors. In essence, this research article serves as a beacon illuminating the path towards a harmonious integration of digital technologies and safety imperatives within the organizational milieu. By fostering a deeper understanding of the dynamics at play and delineating pragmatic strategies for navigating this terrain, the study endeavors to empower organizations to embark on their digital transformation journeys while safeguarding the well-being and resilience of their workforce.